EVALUASI DIKLAT CALON KEPALA MADRASAH - Kun Mawardi Rahayu; Abdul Kadir Ahmad (Balai Diklat Keagamaan Jakarta, 2023)
Abstract The training and education of future madrasah heads are one of the government's efforts to improve the quality of madrasah education. However, during the implementation of this training, there has been no documentation of the number of training alumni who have been appointed as madrasa heads, as mandated by Minister of Religious Affairs Regulation No. 24 of 2018. Yet, the implementation of this training requires considerable resources in terms of both time and finances. This evaluation study aims to qualitatively assess the outcomes of the training and the effectiveness of the alumni in their roles as madrasa heads. Conceptually, the survey measured two main parameters: (1) Evaluation of the training program for prospective madrasa principals, and (2) Performance of madrasa heads. The survey respondents consisted of alumni of the training program from 2018 to 2021 and madrasah educators, with limited characteristics and numbers. The research findings indicate that the alumni who have been appointed as madrasa principals have performed exceptionally well, as they have demonstrated relevance and effectiveness in addressing the challenges faced in the field. According to the alumni and madrasah educators, the performance of madrasa heads is rated as very good. The qualitative research findings also suggest that the process of appointing madrasa heads has followed the procedures established by Minister of Religious Affairs Regulation No. 24 of 2018, although there are some challenges that have hindered the appointment of several alumni as madrasa heads. Abstrak Diklat calon kepala madrasah merupakan salah satu usaha pemerintah dalam meningkatkan mutu madrasah. Namun selama pelaksanaan diklat tersebut, belum ada pendataan jumlah alumni diklat yang sudah terangkat sebagai kepala madrasah sebagai implementasi Peraturan Menteri Agama No 24 Tahun 2018. Padahal pelaksanaan diklat ini membutuhkan biaya dan waktu yang tidak sedikit. Penelitian evaluasi ini dilakukan dengan menggunakan metode kualitatif dengan memperdalam hasil dari diklat yang telah dilakukan dan apakah kinerja dari para alumni diklat efektif. Secara konseptual, parameter yang diukur dalam survei ini terdiri dari 2 parameter besar, yaitu (1) Evaluasi Diklat calon kepala madrasah, dan (2) Kinerja Kepala Madrasah. Responden survei ini adalah alumni diklat calon kepala madrasah 2018-2021 dan tenaga pendidik madrasah, dengan karakteristik dan jumlah yang terbatas. Hasil penelitian menunjukkan bahwa alumni diklat yang telah diangkat menjadi kepala madrasah berada pada kategori Sangat Baik, karena telah relevan dan sesuai tantangan yang hadapi di lapangan. Menurut para alumni diklat dan tenaga pendidik kinerja kepala madrasah Sangat Baik. Hasil penelitian kualitatif menunjukkan bahwa proses pengangkatan kepala madrasah sudah mengikuti prosedur yang telah di tetapkan oleh PMA Nomor 24 Tahun 2018, meskipun ada beberapa kendala yang membuat beberapa alumni Diklat masih belum di angkat menjadi kepala madrasah.